2018
DOI: 10.1097/ta.0000000000001776
|View full text |Cite
|
Sign up to set email alerts
|

Use of open and endovascular surgical techniques to manage vascular injuries in the trauma setting: A review of the American Association for the Surgery of Trauma PROspective Observational Vascular Injury Trial registry

Abstract: III, Therapeutic/care management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…Forward endovascular management at MTFs mimics the practice observed in civilian medicine, in which endovascular approaches are increasingly common and have been shown to provide improved survival and lower complication rates in certain situations. 22,23,[29][30][31] Johnson et al 31 reported finding an additional vascular injury in more than half (53%) of patients who had sustained a combat-related vascular injury by liberally using angiography after evacuation to the United States; 50% required surgical repair. In another review of injury patterns between 2001 and 2004 by Fox et al, 19 the most common indication for arteriography was mechanism of injury (42%), followed by abnormal examination finding (33%), operative planning (18%), or evaluation of a repair (7%).…”
Section: Discussionmentioning
confidence: 99%
“…Forward endovascular management at MTFs mimics the practice observed in civilian medicine, in which endovascular approaches are increasingly common and have been shown to provide improved survival and lower complication rates in certain situations. 22,23,[29][30][31] Johnson et al 31 reported finding an additional vascular injury in more than half (53%) of patients who had sustained a combat-related vascular injury by liberally using angiography after evacuation to the United States; 50% required surgical repair. In another review of injury patterns between 2001 and 2004 by Fox et al, 19 the most common indication for arteriography was mechanism of injury (42%), followed by abnormal examination finding (33%), operative planning (18%), or evaluation of a repair (7%).…”
Section: Discussionmentioning
confidence: 99%
“…REBOA is an important resuscitative tool that ultimately prevents hemodynamic collapse while at the same time maintains coronary and cerebral perfusion in hemodynamically unstable trauma patients, and due to its less invasive nature, it has become an alternative to resuscitative thoracotomy [9][10][11][12][13][14][15][16] . Hörer et al proposed the concept of Endovascular Resuscitation and Trauma Management, a vision that integrates a multidisciplinary patient-centered approach that achieves prompt and effective hemorrhage control with significantly less surgical insult 6,17 .…”
Section: Discussionmentioning
confidence: 99%
“…They can be used as part of a temporary procedure with the objective of avoiding blood loss exsanguination, followed by a definitive treatment, as described here, or treatment may even be definitive in selected cases. 16…”
Section: Discussionmentioning
confidence: 99%